2007
DOI: 10.1113/jphysiol.2006.124800
|View full text |Cite
|
Sign up to set email alerts
|

Fetal body weight and the development of the control of the cardiovascular system in fetal sheep

Abstract: Reduced birth weight predisposes to cardiovascular diseases in later life. We examined in fetal sheep at 0.76 (n = 18) and 0.87 (n = 17) gestation whether spontaneously occurring variations in fetal weight affect maturation of autonomic control of cardiovascular function. Fetal weights at both gestational ages were grouped statistically in low (LW) and normal weights (NW) (P < 0.01). LW fetuses were within the normal weight span showing minor growth dysproportionality at 0.76 gestation favouring heart and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 55 publications
4
74
2
Order By: Relevance
“…Other studies have little to no variation in GA, or their results lack the temporal resolution required to compare results with our findings directly (16,17,30,31). Second, the discrepancies may be the result of methodological differences.…”
Section: Maturational Effects Of Baroreflex Activitycontrasting
confidence: 48%
See 2 more Smart Citations
“…Other studies have little to no variation in GA, or their results lack the temporal resolution required to compare results with our findings directly (16,17,30,31). Second, the discrepancies may be the result of methodological differences.…”
Section: Maturational Effects Of Baroreflex Activitycontrasting
confidence: 48%
“…Other studies found a decrease in baroreflex sensitivity during development (30)(31)(32). Several studies showed no significant maturation of the baroreflex sensitivity (16,17). There may be several explanations for these conflicting findings.…”
Section: Maturational Effects Of Baroreflex Activitymentioning
confidence: 57%
See 1 more Smart Citation
“…RMSSD is the square root of the mean of the sum of the squares of differences between adjacent R-R intervals of ECG. RMSSD is a linear short-term measure of fHRV that reflects modulations of fHRV by vagal activity and was calculated as described earlier (6,7,8). To assess the contribution of sympathetic and vagal modulations to linear and nonlinear fHRV properties, we also studied the complexity of the fHRV with its linear and nonlinear parts.…”
Section: Methodsmentioning
confidence: 99%
“…The fHRV was further analyzed as described earlier (8). Briefly, the artifacts were visually controlled for and removed manually (Watisa Signal Processing Software, Institute for Medical Statistics and Documentation, University of Jena).…”
Section: Methodsmentioning
confidence: 99%